Development and content validity of a website for patients with coronary artery disease - Luiz Felipe Gonçalves Arroio; Juliana de Lima Lopes; Alba Lúcia Bottura Leite de Barros; Edvone Alves de Lima; Camila Tákao Lopes; Vinicius Batista Santos (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to develop and analyze content validity evidence of a website for patients with coronary artery disease. Methods: a methodological study, carried out in the phases: Definition - determined contents for inclusion in the website, architecture and design; Implementation - subjects included in the website; Assessment - website submitted to analysis by 13 experts and eight laypersons regarding organization, content and design, on a scale of 1 (no agreement) to 4 (complete agreement). Items that reached Content Validity Ratio (CVR) higher than the established critical values and Content Validity Index greater than 0.80 were considered valid. Results: eight domains related to secondary prevention in coronary heart disease were included on the website. Critical CVR and adequate CVI were obtained according to professional and lay experts. Conclusions: the website was developed, achieving adequate content validity evidence, and can be used as an educational tool for this population.